2021
DOI: 10.21203/rs.3.rs-555612/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fc-engineered antibody therapeutics with improved efficacy against COVID-19

Abstract: Monoclonal antibodies (mAbs) with neutralizing activity against SARS-CoV-2 have demonstrated clinical benefit in cases of mild to moderate SARS-CoV-2 infection, substantially reducing the risk for hospitalization and severe disease1-4. Treatment generally requires the administration of high doses of these mAbs with limited efficacy in preventing disease complications or mortality among hospitalized COVID-19 patients5. Here we report the development and evaluation of Fc-optimized anti-SARS-CoV-2 mAbs with super… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…Thus, the investigators demonstrated that protection offered by a less potent but more broadly neutralizing nAb could be improved through Fc engineering for enhanced binding to activating FcgRs. This supports other studies demonstrating Fc-FcgR-dependent protection by anti-SARS-CoV-2 antibodies (Ravetch et al, 2021;Winkler et al, 2021). A caveat to these studies was the use of human IgGs in mice that express murine FcgRs along with Fc mutations that enhance binding to human activating FcgRs but that are not well characterized for activity in the mouse system.…”
Section: Llsupporting
confidence: 84%
See 1 more Smart Citation
“…Thus, the investigators demonstrated that protection offered by a less potent but more broadly neutralizing nAb could be improved through Fc engineering for enhanced binding to activating FcgRs. This supports other studies demonstrating Fc-FcgR-dependent protection by anti-SARS-CoV-2 antibodies (Ravetch et al, 2021;Winkler et al, 2021). A caveat to these studies was the use of human IgGs in mice that express murine FcgRs along with Fc mutations that enhance binding to human activating FcgRs but that are not well characterized for activity in the mouse system.…”
Section: Llsupporting
confidence: 84%
“…There is an interesting distinction between the increased protection and absence of inflammation provided by Fc-enhanced nAbs and the enrichment of afucosylated antibodies in patients with severe COVID-19. Further studies are required to dissect the role that afucosylated, polyclonal immune complexes may have in promoting a pathological, early inflammatory response to the infection compared to the protection that can clearly be afforded by monoclonal antibodies that are engineered for enhanced activating FcgR affinity (Ravetch et al, 2021).…”
Section: Llmentioning
confidence: 99%
“…Nonetheless, mutations in the B.1.617.2 alter key antigenic sites and can abrogate recognition by neutralizing antibodies ( 26 ). Other possible explanations for the loss of potency of antibodies against B.1.617.2 include differential display of B.1.617.2 spike proteins on the surface of infected cells and engagement of Fc effector functions ( 27 , 28 ) or differential ability of antibodies to block cell-to-cell spread in a strain-dependent manner ( 29 ). Our observation of B.1.617.2 infection and lung disease in low-dose mRNA-vaccinated K18-hACE2 mice corresponds to descriptions of B.1.617.2 breakthrough infections in vaccinated humans, some of which have required hospitalization ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…While neutralizing antibodies represented an early robust surrogate of immunity prior to the evolution of VOCs, vaccine breakthroughs are rapidly emerging globally in the absence of concurrent levels of disease [ 10 12 ]. Moreover, vaccines afford protection against severe disease and death prior to the evolution of neutralization [ 14 16 ] as well as in the setting of waning immunity [ 17 ], suggesting that alternate immunological mechanisms may exist, which provide protection against disease, including antibody-mediated Fc effector functions [ 18 21 ] and T cells [ 22 26 ], which appear to be less affected by VOCs [ 9 , 27 ]. However, how neutralization, Fc effector function, and T cells collectively contribute to durable and effective protection against SARS-CoV-2 and emerging variants remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%